Prolonged diagnostic delay in acromegaly is associated with increased morbidity and mortality - Esposito, Daniela; Ragnarsson, Oskar; Johannsson, Gudmundur; Olsson, Daniel S (European journal of endocrinology, 2020)
Clinical features of acromegaly develop insidiously. Its diagnosis may therefore be delayed. Our aim was to study diagnostic delay and its impact on morbidity and mortality in a nationwide cohort of patients with acromegaly. Adult patients diagnosed with acromegaly between 2001 and 2013 were identified in the Swedish National Patient Registry. Diagnostic codes for predefined comorbidities associated with acromegaly were recorded between 1987 and 2013. Diagnostic delay was calculated as the time between the first registered comorbidity and the diagnosis of acromegaly. A total of 603 patients (280 men, 323 women) with acromegaly were included. Mean (s.d.) diagnostic delay was 5.5 (6.2) years (median (minimum, maximum) 3.3 (0.0-25.9)) Diagnostic delay was 1-<5 years in 23% patients; 5-<10 years in 17%; and ≥10 years in 24%. No delay was recorded in 36% of patients. Overall, mean (s.d.) number of comorbidities was 4.1 (2.5) and was higher in patients with longer diagnostic delay (P < 0.0001). Overall, observed number of deaths was 61 (expected 42.2), resulting in a standardized mortality ratio (SMR) of 1.45 (95% CI: 1.11-1.86). Increased mortality was only found in patients with the longest diagnostic delay (1.76, 95% CI: 1.12-2.65). In the other groups, no statistically significant increase in mortality was recorded, with the numerically lowest SMR observed in patients without diagnostic delay (1.18; 95% CI: 0.68-1.92). The diagnosis of acromegaly is delayed in most patients. Prolonged diagnostic delay is associated with increased morbidity and mortality.